Nucleation basic theory with applications - Kashchiev, Dimo
This book represents a detailed and systematic account of the basic principles, developments and applications of the theory of nucleation. The formation of new phases begins with the process of nucleation and is, therefore, a widely spread phenomenon in both nature and technology. Condensation and evaporation, crystal growth, electrodeposition, melt crystallization, growth of thin films for microelectronics, volcano eruption and formation of particulate matter in space are only a few of the processes in which nucleation plays a prominent role. The book has four parts, which are devoted to the.